-2(4-x)=-(x+6)

Simple and best practice solution for -2(4-x)=-(x+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(4-x)=-(x+6) equation:


Simplifying
-2(4 + -1x) = -1(x + 6)
(4 * -2 + -1x * -2) = -1(x + 6)
(-8 + 2x) = -1(x + 6)

Reorder the terms:
-8 + 2x = -1(6 + x)
-8 + 2x = (6 * -1 + x * -1)
-8 + 2x = (-6 + -1x)

Solving
-8 + 2x = -6 + -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
-8 + 2x + x = -6 + -1x + x

Combine like terms: 2x + x = 3x
-8 + 3x = -6 + -1x + x

Combine like terms: -1x + x = 0
-8 + 3x = -6 + 0
-8 + 3x = -6

Add '8' to each side of the equation.
-8 + 8 + 3x = -6 + 8

Combine like terms: -8 + 8 = 0
0 + 3x = -6 + 8
3x = -6 + 8

Combine like terms: -6 + 8 = 2
3x = 2

Divide each side by '3'.
x = 0.6666666667

Simplifying
x = 0.6666666667

See similar equations:

| (8.5+x)/2=3.5 | | 5w+2=w+5 | | -7y-7=3y+23 | | 4x+3x-3+5x+3=180 | | 4(2x+7)=2(x-3)+2 | | 2x-1/3=4/3x-1 | | 6(7x-1)-5=42x-11 | | 7x+7=40 | | 7.2-3=.07X | | 7-1x2/3x6 | | 3(2)/(-4)=0 | | .03-(2g+3)=1.8 | | 3-5x=1-6x | | -6y-2=5y-3 | | 3(2x-4)=3x-33 | | x+x+0.56x=28.6 | | 3(2)(-4)=0 | | -3(x+3)+3=-6 | | 2c-5=2c+5 | | 720-3=7X | | 3(4x+8)=-31+43 | | 8(x+2)+6=22 | | 225000x+x=600000000 | | 6(x+7)-26=6x | | Ax-5b=2c | | X-3/3=2x-1/4 | | y/2.53=-5 | | 2x-9=-3x+36 | | -7p-(4-9p)=-10+25p/4 | | 5b+7+7=7+6b | | X^2=.035 | | -72XY^2+45X^2Y= |

Equations solver categories